Electrical conductivity, porosity and density of 12 gravity cores from RV MARIA S. MERIAN cruise MSM111 - von Dobeneck, Tilo; Kucera, Michal; Faust, Johan C (PANGAEA, 2025)
All sediment series recovered during MERIAN Cruise MSM 111 by gravity coring were subject to routine electrical conductivity logging, which was performed on the closed full, and largely pore-water-saturated core segments. The electrical conductivity σs or resistivity Rs (=1/σs) of marine sediment is primarily determined by porosity, pore-water saturation, pore-water salinity, and temperature, while electrically conducting matrix components such as clays are of a minor relevance. The electrical conductivity σs was determined using an inductive non-contact sensor. The system applies high-frequency magnetic fields by a transmitter coil inducing electrical eddy currents in the sediment which are proportional to conductivity. Their secondary field is recorded and yields raw, calibrated and temperature-corrected (T=20°C) values for conductivity and resistivity. Porosity was calculated according to the empirical Archie's equation Rs/Rw = k·φ^(-m) where the ratio of sediment resistivity Rs and pore water resistivity Rw can be approximated by a power function of porosity φ. Values of 1.30 and 1.45 were used for the constants k and m, respectively. The calculated porosity φ is subsequently converted to wet bulk density ρwet by ρwet = φ·ρf + (1 - φ)·ρm (with a pore water density ρf of 1030 kg/m3 and a matrix density ρm of 2670 kg/m3. The MARUM Multi-Sensor Core Logging System (MSCLS) is mounted with a commercial Geotek non-contact-resistivity (NCR) sensor. For the necessary NCR calibration a set of saline solutions at concentrations of 0.35 - 1.75 - 3.5 - 8.75 - 17.5 - 35 g/l was recorded daily. The resistivity sensor averages over approximately 12 cm core length. The core segment data were numerically corrected for (geometry-related) signal decay within the first and last 14 cm of each segment to ideally create seamless records. Nevertheless, conductivity data of the first and last 5 cm of each segment had to be discarded, as they usually showed artifacts of partial pore-water and/or sediment loss.
Keywords: Conductivity; density; MSM111; porosity; Sediment core